Religious Moderation Education in Practice: A Study on International Students in a Middle Eastern University Dormitory - Nuha Sufina Binti Saidi; Nur Akashah Binti Zulkefli; Dasrizal Dasrizal (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2025)
The international dormitory environment in the Middle East not only serves as a place of residence, but also as a complex socio-cultural and religious space for foreign students. As a residential area, dormitories offer various activities to foster social, emotional, and spiritual intelligence among students. This study aims to explore how various activities in dormitories can be a medium for the practice of religious moderation education. This study uses a qualitative method with an ethnographic approach. Data sources were obtained through in-depth individual and group interviews with twenty-five foreign students from five countries, namely Malaysia, Indonesia, China, Nigeria, and Bangladesh. All informants were foreign students living in university international dormitories. To strengthen the interview data, the researchers also conducted direct observations of the activities carried out, and even participated for one year in various activities of foreign students at the research site. All data were analyzed thematically using the qualitative software NVivo 12. The research findings reveal that religious moderation values such as tolerance, empathy, and respect for differences are not taught through formal programs but grow organically and are constructed through interactions in seven dormitory activities, namely i) cultural festivals, ii) clubs or communities, iii) volunteer activities, iv) mentorship programs, v) worship or religious rituals, vi) spiritually-based community service activities, vii) spiritual discussion groups. This finding provides a perspective for universities to function dormitories not only as a place to live, but as an inclusive environment that naturally fosters religious moderation.